Genre Based Approach in Teaching Writing Analytical Exposition Text - Yulianti, Erni (Jurnal Pendidikan Progresif, 2017)
Genre based approach in teaching writing analytical exposition text.This study investigated the Genre-Based Approach (GBA) in teaching writing the analytical exposition text. This study tried to describe GBA application in the class, to know how GBA led to students’ writing analytical exposition text, and to know students’ perception toward GBA in writing analytical exposition text. Data in this study were obtained from questionnaires and pretest-post test. Data from pretest-post test, to know the improvement of the students’ writing analytical exposition text were administered by using Match T-test. The finding revealed that students had positive perception in learning writing analytical exposition text through GBA.  Keywords:genre based approach, writing analytical exposition text, teaching writingDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701